Oceanological and Hydrobiological Studies (De Gruyter, 2007)
Oceanological and Hydrobiological Studies is devoted to topics concerning the water environment, both freshwater and saltwater. The objective pursued by the Journal is to collect and publish in one medium the findings of worldwide studies on various types of water environment and climatic conditions.